2018
DOI: 10.1016/j.toxrep.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of blood chemistry, hepatic and renal function, and blood cytometry in acrylamide-treated rats

Abstract: Acrylamide is a vinyl monomer that is widely used for the synthesis of polyacrylamides, the treatment of drinking water, and as an additive in cosmetics. Acrylamide is also produced during the thermal processing of carbohydrate-rich foods. Although the potential toxic effects of acrylamide have been reported, few studies have evaluated biochemical parameters in blood. The present study investigated alterations of blood chemistry, hepatic function, and blood cytometry in acrylamide-treated rats. Thirty-two male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 27 publications
1
18
1
2
Order By: Relevance
“…In this study, we also measured alanine aminotransferase (ALT) and aspartate transaminase (AST), which are important markers of liver function, in experimental rats treated with the aqueous shoot extract of Y. alpina to determine its effects on liver health and function. Notably, ALT is primarily domiciled in the liver, making it the most sensitive marker of liver damage [ 35 , 36 ]. Even though AST is found in the liver, kidney, and cardiac and skeletal muscles, determining its levels coupled to ALT is vital in diagnosing cell damage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also measured alanine aminotransferase (ALT) and aspartate transaminase (AST), which are important markers of liver function, in experimental rats treated with the aqueous shoot extract of Y. alpina to determine its effects on liver health and function. Notably, ALT is primarily domiciled in the liver, making it the most sensitive marker of liver damage [ 35 , 36 ]. Even though AST is found in the liver, kidney, and cardiac and skeletal muscles, determining its levels coupled to ALT is vital in diagnosing cell damage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to environmental toxins is one of the four best-documented pan cellular factors besides age, genetic mutations and inflammation leading to increasing the risk of developing PD [28]. Acrylamide is a common chemical that is widely used for synthesis of polyacrylamide, treatment of drinking water and as cosmetic additives, and forms in many of high temperature prepared carbohydrate-rich foods [23]. Although ACR has been documented as a neurotoxic substance since the 1950s, no studies have shown its effects on dopaminergic neurons, the cells that synthesize the dopamine neurotransmitter and their loss leads to PD, yet.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensively distributed evidence suggestive of the significance of blood chemistry in a clinical manifestation of chemical-induced nephrotoxicity [ 32 ]. Earlier data also demonstrated that alterations in normal kidney functions are associated with significant changes in the levels of several blood biomarkers of nephrotoxicity, namely BUN, serum cholesterol, and phospholipid levels s [ 54 ]. In our study, we revealed that the injection of cisplatin considerably affected the serum levels of BUN, serum cholesterol, and phospholipid.…”
Section: Discussionmentioning
confidence: 99%